Morphometric analysis of the hominin talus: Evolutionary and functional implications. Issue 142 (May 2020) - Sorrentino, Rita; Carlson, Kristian J.; Bortolini, Eugenio; Minghetti, Caterina; Feletti, Francesco; Fiorenza, Luca; Frost, Stephen; Jashashvili, Tea; Parr, William; Shaw, Colin; Su, Anne; Turley, Kevin; et al.
Abstract: The adoption of bipedalism is a key benchmark in human evolution that has impacted talar morphology. Here, we investigate talar morphological variability in extinct and extant hominins using a 3D geometric morphometric approach. The evolutionary timing and appearance of modern human–like features and their contributions to bipedal locomotion were evaluated on the talus as a whole, each articular facet separately, and multiple combinations of facets. Distinctive suites of features are consistently present in all fossil hominins, despite the presence of substantial interspecific variation, suggesting a potential connection of these suites to bipedal gait. A modern human–like condition evolved in navicular and lateral malleolar facets early in the hominin lineage compared with other facets, which demonstrate more complex morphological variation within Homininae. Interestingly, navicular facet morphology of Australopithecus afarensis is derived in the direction of Homo, whereas more recent hominin species such as Australopithecus africanus and Australopithecus sediba retain more primitive states in this facet. Combining the navicular facet with the trochlea and the posterior calcaneal facet as a functional suite, however, distinguishes Australopithecus from Homo in that the medial longitudinal arch had not fully developed in the former. Our results suggest that a more everted foot and stiffer medial midtarsal region are adaptations that coincide with the emergence of bipedalism, whereas a high medial longitudinal arch emerges later in time, within Homo . This study provides novel insights into the emergence of talar morphological traits linked to bipedalism and its transition from a facultative to an obligate condition.